Incidence and Causes of Injury Deaths among Children under Five Years of Age in El-Giza -Egypt - Gad Allah, Ahmed Mohmed (Journal of medical and pharmaceutical sciences, 2019)
Objectives: To study the incidence and causes of injury mortality among children under the age of five years in El-Giza. Setting: The study was conducted in El-Giza, Egypt, the second largest city with a population of 8.7 million for 2017. It comprises urban and semiurban settlements. Methods: A descriptive epidemiological study, which obtained information about all deaths using a questionnaire from 197 Health Centres for one year, 2017. Subjects were residents who died from unintentional and intentional injuries. Results: The overall under fives crude mortality rate was 3.1 per1000. The number of children deaths from injuries was 309(8.7% of all deaths), more among males than females (31.5 υ 23.1 per 100 000). Those under 1 had the highest rate, 32.7 per 100 000. The top three causes of deaths were traffic accidents (31.7%), falls (18.8%), and drowning (11%). Conclusions: Injury is the common cause of deaths among children under five years of age in El-Giza. Because all age groups and both sexes are victims of injuries, and most unintentional injuries are preventable, they must be considered as a priority health problem in El-Giza. More studies are needed in rural areas of Egypt. Recommendations: It is important that child health community in Egypt and in other developing countries enhances its focus on injury as a child health issue and integrate injury prevention efforts in child health policies and programmers.